Relationships among postural stability, physical fitness, and shooting accuracy in Olympic female goalball players - Makaraci, Y.; Nas, K.; Pamuk, Ö.; Aydemir, M. (Journal of Exercise Rehabilitation, 2022)
This study aims to examine the relationship between postural performance, physical fitness level, and shooting performance in Olympic female goalball players. Eight Olympic-level goalball players (age: 20.63± 4.37 years) were recruited from the Turkish National Women`s Goalball Team. Postural stability, physical fitness, and shooting performance of the players were measured. The postural stability was determined using body sway measurements during parallel and single-leg stances on a force plate. The physical fitness level of the players is evaluated by curl-up, isometric push-up, trunk lift, and grip strength (dominant hand) tests. A goalball-specific shooting accuracy test was used for shooting performance. Independent sample t-test and Pearson correlation were used for statistical processing. No statistical difference was observed in body sway parameters between open eyes and closed eyes conditions except for the anteroposterior sway area. Some of the body sway parameters performed under different stances positively correlated with all physical fitness tests (P<0.05). There was a positive correlation between the shooting accuracy and trunk lift score (r=0.767). Right leg sway area anterior-posterior and ellipse area negatively correlated with shooting accuracy (r=-0.629 and r=-0.692 respectively). It is necessary to attach importance to the improvement of the physical fitness level specific to core strength to maintain postural stability for visually im-paired athletes. In our study, some factors affecting shooting accuracy were identified, but it is necessary not to restrict a complex structure such as shooting accuracy within certain concepts.